Givens
x + y = 3
x =6 - 4y
Solution
Use the top equation to substitute for x in the second equation.
x = 3 - y
Put this result into the second given equation and solve for y
3 - y = 6 - 4y Add 4y to both sides.
3 - y + 4y = 6 Combine on the left
3 + 3y = 6 Subtract 3 from both sides
3 - 3 + 3y = 6 - 3 Combine
3y = 3 Divide by 3
3y/3 = 3/3 Combine
y = 1
=========================
x + y = 3 but y = 1
x + 1 = 3 Subtract 1 from both sides.
x + 1 - 1 =3 - 1
x = 2
Answer
x = 2
y = 1
Answer:
C
Step-by-step explanation:
you add c to both side which will then make it 7x=k+c then you would divide 7 from both sides leaving you with x=k+c/7. Except 7 will be under the k and c.
This is in slope-intercept form which is y=mx+b
where m is the slope and b is the intercept
in this equation -7 is m
The correct answer is -7